Faʿāliyatu Istikhdām Wasīlati Wordsearch fī Taḥsīni Mahārat al-Kitābah ladā Ṭullāb al-Ṣaff al-Sābiʿ fī Madrasah al-Washliyah al-Thānawiyyah al-Ahliyah Pantai Cermin (Taqdir, 2025)
Students of Grade VII at MTs Al-Washliyah Pantai Cermin encounter difficulties in writing Arabic words, primarily due to their inability to recognize the forms of Arabic letters (huruf hijaiyah) when connected to other letters. To address this issue, an appropriate learning medium is required. This study aims to investigate the effectiveness of the Wordsearch game in improving the Arabic writing skills (maharah al-kitabah) of Grade VII students at MTs Al-Washliyah. The research employed a quantitative approach with a quasi-experimental design. The sample consisted of 60 Grade VII students. Data were collected through written assessments, including pre-tests and post-tests. Data analysis techniques involved normality tests, homogeneity tests, t-tests, and N-Gain tests. The results demonstrated a significant improvement in students’ writing skills following the application of the Wordsearch game. The t-test results showed a significance value of <0.001 (<0.05). It is concluded that the Wordsearch game is effective in enhancing students' maharah al-kitabah